2014
DOI: 10.1538/expanim.63.247
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin C-Terminal Hydrolase L1 Is Expressed in Mouse Pituitary Gonadotropes <i>In Vivo</i> and Gonadotrope Cell Lines <i>In Vitro</i>

Abstract: The ubiquitin-proteasome system (UPS) plays a fundamental role in regulating various biological activities. Ubiquitin C-terminal hydrolase L1 (UCH-L1) is a deubiquitinating enzyme, belonging to the UPS. To date, it has been reported that UCH-L1 is highly and restrictedly expressed in neural and reproductive tissues and plays significant roles in these organs. Although the expression of UCH-L1 in the anterior pituitary gland has been reported, the detailed localization and the role of UCH-L1 remain obscure. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This analysis shows that two endogenous pituitary cell populations, FSC and HPC, express several common marker genes, including Pitx1, Pitx2 , and some neuroendocrine markers, but each population is also characterized by specific marker genes. Consistent with the literature, our analysis confirms that Resp18 (50) , Uchl1 (51), and Snap25 (52) are good cell markers for all HPC. It has been reported that Chgb (53), Ptprn2 (54), Scg2 (55), and Syp (56) are expressed in some HPC types, but here we show that these genes are marker genes for all HPC.…”
Section: Discussionsupporting
confidence: 91%
“…This analysis shows that two endogenous pituitary cell populations, FSC and HPC, express several common marker genes, including Pitx1, Pitx2 , and some neuroendocrine markers, but each population is also characterized by specific marker genes. Consistent with the literature, our analysis confirms that Resp18 (50) , Uchl1 (51), and Snap25 (52) are good cell markers for all HPC. It has been reported that Chgb (53), Ptprn2 (54), Scg2 (55), and Syp (56) are expressed in some HPC types, but here we show that these genes are marker genes for all HPC.…”
Section: Discussionsupporting
confidence: 91%
“…However, immunogold electron microscopy for PDGFRĪ² shows that it is localised to cells with ultrastructural characteristics of both folliculostellate cells and pericytes. Previous studies (including those using the same antibody as that employed in the present study) have shown S100 staining in the pituitary, 28ā€34 although these S100ā€positive cleft cells are often defined as ā€˜folliculostellate cellsā€™ but do not show staining throughout the parenchyma. Interestingly, Allaerts et al 35 note that they do not observe S100 staining in the mouse pituitary.…”
Section: Discussionmentioning
confidence: 59%
“…For example, GFAP is expressed in the gastrointestinal tract and the liver ( 58 ), BDNF and NSE are concentrated in platelets ( 59 , 60 ) and S100b is expressed in adipocytes and the GI tract ( 61 , 62 ). Similarly, ubiquitin carboxy terminal hydrolase-L1 (UCH-L1, PGP9.5), an emerging prototype TBI biomarker, is expressed in the endometrium and secretory cells of the pituitary gland ( 63 ā€“ 66 ). Accordingly, the concept of a brain-specific response must be qualified when considering TBI biomarker proteins and should include the potential contribution of poly trauma to a biomarker signature.…”
Section: Discussionmentioning
confidence: 99%